Hygienic Assessment of Child Growth and Development in the Context of Preschool Education Reform - Salikhovna, Yadgarova Shakhodat (European Journal of Life Safety and Stability (2660-9630), 2022)
In the Republic of Uzbekistan, the contingent of children and adolescents is the main part of the population. The contingent of children and adolescents, particularly in rural areas, accounts for 34-40 percent of the entire population. The state of Health and physical development indicators of those entering this category of the population cannot be called satisfactory. One of the main reasons for this is inappropriate social hygienic conditions. Today, coverage of children in pre-school educational institutions in our republic is 35%. Along with this, some preschool institutions do not meet hygienic requirements with such conditions as the condition of the building, equipment, Organization of feeding. Along with this, the level and quality of medical services provided to children and adolescents are not in demand. Therefore, the death rate in early childhood to evazi is 33 units per 1000 live births .Inappropriate conditions in some pre-school educational institutions of the Republic ,their low coverage by these institutions ,inadequate communal living conditions in their places of residence, adversely affected their growth and development , led to an increase in some diseases among them . It should be separately recognized that the peculiarities of the organism of growing children, their very rapid permeability and sensitivity to harmful effects, necessitate the creation of sufficient conditions for their harmonic growth and development